VD_FINDINFO Décision / 2013 / 558 vom 19. Juni 2013 - VD Tribunal cantonal (2013)
DÉCISION D'IRRECEVABILITÉ, ESCROQUERIE, ASTUCE, AVANCE DE FRAIS | 146 al. 1 CP, 310 CPP (CH), 393 al. 1 let. b CPP (CH)